Ambient air pollution and children’s health: A systematic review of Canadian epidemiological studies - Koranteng, Samuel (Pulsus Group Inc, 2007)
BACKGROUND: There is growing concern about the health effects of ambient air pollution (AP) in children. The present article summarizes and compares local information regarding the adverse effects of AP on the health of Canadian children with reports from elsewhere. METHODS: PUBMED, MEDLINE and EMBASE databases were searched for epidemiological studies, published between January 1989 and December 2004, on the adverse health effects of criteria air pollutants among Canadian children. RESULTS: Eleven studies investigated the association between AP and various respiratory health outcomes, while one study assessed the effect of AP on sudden infant death syndrome. Another study examined the effects of AP on pregnancy outcomes. Most of the available information was from Ontario and British Columbia. Despite inconsistencies among study results and data from elsewhere, evidence from Canadian studies suggest that AP may cause adverse respiratory health effects in children and adverse pregnancy outcomes, and may contribute to infant mortality in Canada. INTERPRETATION: AP has detrimental health effects among Canadian children. Paediatricians and other health care workers with an interest in child health should encourage parents and children to adhere to smog (AP) advisories. Existing regulatory practices should be reviewed to reduce current levels of ambient air pollutants in Canada.